Peningkatan Nilai Tambah Durian Afkir melalui Produksi Dodol Durian di Kuala Selangor Malaysia - Sandro Aldy; Prayoga Suryadarma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Malaysia is the second largest country as a producer of durian. The more days pass, consumer demand for durian is increasing but in fact not all durians are good quality. Watery durian is one type of rejected durian that is often found in Malaysia and not many people like it. This study aims to analyze the added value of processed products. The commodity processed products analyzed are good quality durian and watery durian. The business analysis method used includes the analysis of costs, revenues, profits, and R/C ratio. Added value analysis using the Hayami method. The value added analysis results of watery durian dodol products is RM 12.48 /kg where each RM 100 product value contains an added value of RM 48.75. Watery durian dodol is a potential business to be applied starting from small to large scale and can overcome the wasted watery durian fruit.